Developmentally regulated alternative RNA splicing of rat brain sodium channel mRNAs. - Sarao, R (1991)
Two rat brain Na channel alpha-subunit cDNAs, named RII and RIIA, have almost identical coding regions, with a divergence of only 36 nucleotides (0.6%) over a total length of 6015 residues. A cluster of 20 divergent residues occurs within a 90 nucleotide segment of cDNA sequence. We now demonstrate that this 90 nucleotide segment is encoded twice in the RII/RIIA genomic sequence. Furthermore, the mutually exclusive selection of these two exons is developmentally regulated. RII mRNAs are relatively abundant at birth but are gradually replaced by RIIA mRNAs as development proceeds. The two mRNAs also appear to have different regional distributions in the developing rat brain. Strikingly, although 30 amino acids are encoded by each alternative exon, only amino acid position 209 is altered between the two, specifying asparagine in RII and aspartate in RIIA. Alternative RNA splicing may modulate the RII/RIIA sodium channel properties during neuronal development.